Desenvolvimento e avaliação de sistemas automicroemusionáveis contendo carvedilol pela técnica de termoextrusão - Silva, Luís Antônio Dantas (2017)
Introduction: Self-emulsifying drug delivery systems (SMEDDS) have been successfully used as carriers for poorly water-soluble drugs, because they can effectively solubilize them, as well as stimulate their intestinal lymphatic transport, reduce first-pass metabolism, and inhibit efflux proteins present in intestinal cells. All these effects together contribute to the improvement in the oral bioavailability of the incorporated drugs. The preparation of solid self-emulsifying systems is associated with additional advantages, such as increased stability, ease of transport, storage, and administration. Hot-melt extrusion is a technique that has attracted great interest in the pharmaceutical industry in recent years for enabling continuous production of solid dosage forms, with high productivity and low cost. In addition, it can be performed without the use of solvents. Despite this, there are no reports in the literature about the use of this technique in the production of solid self-emulsifying systems. Objectives: The objective of the present work was to perform preformulation studies and to develop solid self-microemulsifying systems containing carvedilol by hot-melt extrusion, aiming at improving the dissolution of this drug. Methods: Initially, carvedilol solubility and compatibility in different lipid excipients were determined, respectively, by the equilibrium solubility method and thermoanalytical, spectroscopic and isothermal stress techniques. An analytical method was developed and validated to carvedilol quantitation by high performance liquid chromatography. Next, the selected excipients were used in the construction of a ternary phase diagram, in order to determine the best ratio for SMEDDS production. Finally, the selected liquid formulation was mixed with a polymeric system consisting of an enteric polymer (hydroxypropylmethylcellulose acetate succinate) and other excipients. The resulting mixture was extruded in a twin screw hot-melt extruder. Box-Behnken factorial design was used to evaluate the effects of formulation (carvedilol concentration) and process variables (temperature and recirculation time) on the release of the drug (in 0.1 M HCl and phosphate buffer pH 6.8) and redispersion of the microemulsion from the solid system. The extrudates’ morphology was evaluated by light microscopy and scanning electron microscopy and the physical state of the drug in the preparation was investigated by differential scanning calorimetry and X-ray powder diffraction. Results: Preformulation studies showed that carvedilol is incompatible with the lauric acid, oleic acid, Gelucire® 44/14, Capmul® MCM, canola oil, castor oil, polyethoxylated castor oil, corn oil, soybean oil, sunflower oil and safflower oil. On the other hand, carvedilol was stable in mixtures with sesame oil, Plurol® Isostearique, Transcutol HP®, stearic acid, palmitic acid, Compritol® 888 ATO, Emulium® 22 and with the mixture of capric/caprilic triglycerides (CCT). The CCT showed to be the best solvent for carvedilol (3.93 ± 0.20 mg mL-1), among the compatible lipid excipients. Thus, the mixture of CCT, Plurol® and Transcutol HP® was selected for preparation of the self-emulsifying systems containing carvedilol. The phase diagram showed that the ratio of 50/37.5/12.5 (oil/surfactant/cosurfactant) resulted in the best parameters of self-emulsification (time, clarity and stability) average size (140.04 ± 7.22 nm) and size distribution (0.219 ± 0.011). These values were not significantly altered by the inclusion of carvedilol in the mixture (139.06 ± 7.28 nm and 0.221 ± 0.015). This self-microemulsifying concentrate with polymeric carriers were then extruded and the resulting product was a compact matrix. Factorial design showed that the drug concentration, temperature and recirculation time significantly influenced the drug release in different media, as well as the reconstitution efficiency of the microemulsion. Carvedilol release in acid medium was in the range of 12 to 25% and it was significantly affected by the temperature and recirculation time. The polymeric matrix was able to prevent redispersion of the system in acid. In turn, drug released was significantly affected by drug concentration in pH 6.8, ranging from 43 to 85%. Drug release in this medium was primarily affected by the concentration of the drug in the formulation. The reconstitution efficiency was significantly affected by the circulation time and process temperature, ranging from 55 to 100% in pH 6.8. Average size (145 to 164 nm) and PdI (0.209 to 0.262) were not significantly affected by the studied variables Conclusion: Self-microemulsifying extrudates were prepared from the lipid concentrate selected from the preformulation studies. The solid systems allowed a site-specific microemulsion redispersion, thus presenting potential for lymphatic absorption of carvedilol. The experimental results presented here are the first report about the production of solid self-microemulsifying systems containing carvedilol by hot-melt extrusion.